Data Validation and Scientific Assumption of Impartiality in Accounting by Horkheimer’s Verstand - Nascimento de Araújo, João Gabriel; Matos, Francisco José Sobreira de; Soeiro, Tiago de Moura; Lagioia, Umbelina Cravo Teixeira (Revista de Contabilidade da UFBA, 2023)
In this paper we discuss by Horkheimer’s perspective of instrumental reason (verstand), aspects related to data validation and impartiality in accounting research. In proposing the denial of absolute truth, Adorno & Horkheimer (1985) distinguishes two reasons: Verstand (instrumental reason) and Vernunft (substantial reason). The Verstand, as an expression of modernity and it science, is the character of reason purely formal, operational, ordering data. In other words, Verstand is the idea that the truth is known, or which must first seek a formula to put into practice only after. On the other hand, Vernunft is dialectical reason, a temporary fact, due to historical factors. Through Vernunft is possible to question the unquestionable, overcome the conclusive truth and objective authority. Thus, we show briefly an evolutionary view of accounting in order to highlight the development of accounting thought until a traditional theoretical perspective adopted. Then we make a counterpoint to this traditional perspective by verstand. In our discussion, we claim from researchers a choice between vernunft or verstand and make clear the data limitations into interpretations inside instrumental idea. We do not intend to propose in this article any ways to change the current paradigm in accounting. On the contrary, supported in Adorno (2009) displays as negative dialectics, this article aims solely to foster and mature debate, supported the substantial reason (Vernunft). As a result, by adding the verstand perspective in accounting research some interesting insights and interpretation will be provided by future research. In so doing, we expect a special attention to epistemological position which improve the data validation.